Modeling emoji online marketing on websites among young consumers: the moderation effect of age - Mihlali Maraule; Rodney Duffett; Tudor Edu (Future Business Journal)
Abstract The incorporation of emojis in online marketing can result in positive attitudes toward businesses and brands and purchase intentions among Generation Z consumers. This study aims to integrate various other constructs with Technological Acceptance Model variables to assess emoji online marketing on websites. Additionally, this study will also explore the moderating effect of age on behavioral associations. A sample of 485 Generation Z customers was used to determine the effectiveness of using emojis for online marketing. The study used both a quantitative research strategy and a descriptive research design. A non-probability snowball sampling method was used to gather data from young South African respondents via a self-administered questionnaire. The hypotheses were tested using structural equation modeling. The findings of the research proved a number of favorable associations between customer engagement, perceived usefulness, perceived ease of use, involvement, trust, and purchase intention. Notably, older consumers within the Generation Z cohort demonstrated favorable behavioral attitude associations due to emoji online marketing on websites. The study contributes to the development of a comprehensive Technological Acceptance Model in the context of emoji online marketing. The findings are valuable as younger generations seek businesses and brands that possess a deep understanding of their needs to establish a meaningful engagement with them.